Prospective associations of technostress at work, burnout symptoms, hair cortisol, and chronic low-grade inflammation - Kaltenegger, Helena C.; Marques, Mathew D.; Becker, Linda; Rohleder, Nicolas; Nowak, Dennis; Wright, Bradley J.; Weigl, Matthias (Brain Behavior and Immunity, 2024)
Background: Working conditions in the age of digitalization harbor risks for chronic stress and burnout. However, real-world investigations into biological effects of technostress, that is stress in the context of digital technology use, are sparse. This study prospectively assessed associations between technostress, general work stress, burnout symptoms, hair cortisol, and chronic low-grade inflammation. Methods: Hospital employees (N = 238, 182 females, Mage = 28.5 years) participated in a prospective cohort study with two follow-ups six months apart (T2, T3). Participants answered standardized questionnaires on general job strain (job demand-control ratio), technostressors (work interruptions, multitasking, information overload), burnout symptoms (exhaustion, mental distance), and relevant confounders. Moreover, they provided capillary blood samples for C-reactive protein (CRP) and hair strands for hair cortisol concentration (HCC) analysis. Structural equation modelling was performed. Results: The factorial structure of survey measures was confirmed. Burnout symptoms (MT2 = 2.17, MT3 = 2.33) and HCC (MT2 = 4.79, MT3 = 9.56; pg/mg) increased over time, CRP did not (MT2 = 1.15, MT3 = 1.21; mg/L). Adjusted path models showed that technostress was negatively associated with HCC (β = −0.16, p =.003), but not with burnout and CRP. General work stress in contrast, was not significantly associated with burnout, HCC or CRP. Furthermore, there were reciprocal effects of CRP on HCC (β = 0.28, p =.001) and of HCC on CRP (β = −0.10, p ≤.001). Associations were robust in additional analyses including further confounders. Conclusion: This is the first study on prospective effects of technostress on employees’ endocrine and inflammatory systems. Results suggest differential effects of technostress on the hypothalamic-pituitary-adrenocortical axis activity. Given its key role for long-term health, the findings have important implications for occupational health and safety in digitalized work environments.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Burnout; C-reactive protein; Chronic low-grade inflammation; Digital stress; Hair cortisol; Technostress; Work stress